JURIDICAL REVIEW THE VALIDITY OF THE AGREEMENT ON PEER TO PEER LENDING SERVICES - Ariza Umami; Betha Rahmasari; Yessica Melani (Otentik's : Jurnal Hukum Kenotariatan, 2023)
At this time many new innovations have sprung up that were born from a combination of the financial and technology sectors, one of which is Peer to Peer Lending or online loans. This study aims to find out how the validity of the agreement and the legal consequences that occur in Peer to Peer Lending services. Types of juridical-normative research. In terms of the validity of the agreement it remains generally regulated in article 1320 of the Civil Code, legal consequences occur if the parties to the agreement do not fulfill the terms of the agreement. So, the agreement can be cancelled. If it does not meet the subjective requirements and the agreement is null and void if it does not meet the objective conditions of an agreement.